2003
DOI: 10.1097/01.jom.0000063626.37065.e8
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Work–Family Conflict: A Prospective Cohort Study

Abstract: This study examined both risk factors for the onset of work-family conflict and consequences in terms of need for recovery and prolonged fatigue for men and women separately. Two-year follow-up data from the Maastricht Cohort Study on "Fatigue at Work" (n = 12,095) were used. At baseline, the prevalence of work-family conflict was 10.8% (9.0% in women; 11.1% in men), the cumulative incidence at 1 year follow-up was 5.1%. For men, several work-related demands, shift work, job insecurity, conflicts with coworker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
5
19

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(213 citation statements)
references
References 37 publications
17
172
5
19
Order By: Relevance
“…Van Hooff and co-authors attempted to disentangle these relationships in a longitudinal study from 2005, and found a significantly better fit for the model implying strain-based work-home interference as being the precursor to poor health than the opposite (van Hooff et al, 2005). Another prospective study came to the same conclusion (Jansen et al, 2003), although in both papers it is stated that a reversed causation cannot be ruled out, and that a bi-directional relationship may be at hand.…”
Section: Methodological Considerations and Comparison With Previous Smentioning
confidence: 75%
See 1 more Smart Citation
“…Van Hooff and co-authors attempted to disentangle these relationships in a longitudinal study from 2005, and found a significantly better fit for the model implying strain-based work-home interference as being the precursor to poor health than the opposite (van Hooff et al, 2005). Another prospective study came to the same conclusion (Jansen et al, 2003), although in both papers it is stated that a reversed causation cannot be ruled out, and that a bi-directional relationship may be at hand.…”
Section: Methodological Considerations and Comparison With Previous Smentioning
confidence: 75%
“…Thus, both WFC and FWC affected the mental health of men and women in three countries in the previously mentioned study from 2004(Chandola et al, 2004. As reported above, in the Dutch prospective study, employees reporting such conflict had a higher average number of absent days over six months of follow-up (Jansen et al, 2006) and also a significantly higher risk of developing fatigue and an elevated need for recovery (Jansen, Kant, Kristensen, & Nijhuis, 2003). Frone, in 2000, found that both WFC and FWC were also positively related to clinically significant diagnoses of mood, anxiety, and substance dependence disorders (Frone, 2000).…”
Section: Methodological Considerations and Comparison With Previous Smentioning
confidence: 90%
“…Unfortunately, surprisingly few studies on these outcomes have been conducted. In an earlier study, we found that shiftworkers reported a higher risk of work-family conflict when compared with dayworkers (35). Work-family conflict is a perception of insufficient energy and time to combine work and family roles successfully (36).…”
Section: Derection Of Shift Rotation Health and Work-family Conflictmentioning
confidence: 88%
“…Other studies have also found that work-related factors are related to work-family conflicts such as working overtime, time travelling to work and physical demands 22 . Socioeconomic status and other work-related factors were included to measure their possible effects on the relationship between work -family conflicts and recommended food habits or physical activity.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%